Role of reactive oxygen species in lesion mimic formation and conferred basal resistance to Fusarium graminearum in barley lesion mimic mutant 5386 - Wang, Wenqiang; Zhang, Jifa; Guo, Fenxia; Di, Yindi; Wang, Yuhui; Li, Wankun; Sun, Yali; Wang, Yuhai; Ni, Fei; Fu, Daolin; Wang, Wei; Hao, Qunqun (Frontiers in Plant Science, 2022)
This study investigated the barley lesion mimic mutant (LMM) 5386, evidenced by a leaf brown spot phenotype localized on the chromosome 3H, and its conferred basal resistance to Fusarium graminearum. RNA-seq analysis identified 1453 genes that were differentially expressed in LMM 5386 compared to those in the wild type. GO and KEGG functional annotations suggested that lesion mimic formation was mediated by pathways involving oxidation reduction and glutathione metabolism. Additionally, reactive oxygen species (ROS) accumulation in brown spots was substantially higher in LMM 5386 than in the wild-type plant; therefore, antioxidant competence, which is indicated by ROS accumulation, was significantly lower in LMM 5386. Furthermore, the reduction of glycine in LMM 5386 inhibited glutathione biosynthesis. These results suggest that the decrease in antioxidant competence and glutathione biosynthesis caused considerable ROS accumulation, leading to programmed cell death, which eventually reduced the yield components in LMM 5386.